Analysis of Social Determinants of Health in Justice-Involved Youth: Relevance in the Context of Poverty - Tyrrell, Orla C (2017)
The current study will address the gap in the literature to identify and understand the significant relationship between the social determinants of health and poverty to target the needs of young offenders more effectively by referring youth to agencies and community-based services relevant for successful rehabilitation. The study reviewed 281 assessment files of young offenders at an urban-based court clinic in London, ON. Results indicated a significant relationship between the extent of poverty and compromised social determinants of health. Offending youth who experienced high poverty also demonstrated higher frequencies in experiencing family structure instability, a lack of parent involvement or concern, greater grade failure and lack of educational attainment, lack of organized leisure activities and greater gang affiliation within the community. Additionally, regression analyses indicated that the degree of experienced poverty predicted likelihood of reoffending and gaining access to relevant services. Implications for clinical practice including sensitivity from service workers and further consideration of changes in social policy and response from the justice system are discussed